Selective decline of neurotrophin and neurotrophin receptor genes within CA1 pyramidal neurons and hippocampus proper: Correlation with cognitive performance and neuropathology in mild cognitive impairment and Alzheimer's disease - Ginsberg, Stephen D.; Malek‐Ahmadi, Michael H.; Alldred, Melissa J.; Che, Shaoli; Elarova, Irina; Chen, Yinghua; Jeanneteau, Freddy; Kranz, Thorsten M.; Chao, Moses V; Counts, Scott E.; Mufson, Elliott J. (Hippocampus, 2019)
Hippocampal CA1 pyramidal neurons, a major component of the medial temporal lobe memory circuit, are selectively vulnerable during the progression of Alzheimer's disease (AD). The cellular mechanism(s) underlying degeneration of these neurons and the relationship to cognitive performance remains largely undefined. Here, we profiled neurotrophin and neurotrophin receptor gene expression within microdissected CA1 neurons along with regional hippocampal dissections from subjects who died with a clinical diagnosis of no cognitive impairment (NCI), mild cognitive impairment (MCI), or AD using laser capture microdissection (LCM), custom‐designed microarray analysis, and qPCR of CA1 subregional dissections. Gene expression levels were correlated with cognitive test scores and AD neuropathology criteria. We found a significant downregulation of several neurotrophin genes (e.g., Gdnf, Ngfb, and Ntf4) in CA1 pyramidal neurons in MCI compared to NCI and AD subjects. In addition, the neurotrophin receptor transcripts TrkB and TrkC were decreased in MCI and AD compared to NCI. Regional hippocampal dissections also revealed select neurotrophic gene dysfunction providing evidence for vulnerability within the hippocampus proper during the progression of dementia. Downregulation of several neurotrophins of the NGF family and cognate neurotrophin receptor (TrkA, TrkB, and TrkC) genes correlated with antemortem cognitive measures including the Mini‐Mental State Exam (MMSE), a composite global cognitive score (GCS), and Episodic, Semantic, and Working Memory, Perceptual Speed, and Visuospatial domains. Significant correlations were found between select neurotrophic expression downregulation and neuritic plaques (NPs) and neurofibrillary tangles (NFTs), but not diffuse plaques (DPs). These data suggest that dysfunction of neurotrophin signaling complexes have profound negative sequelae within vulnerable hippocampal cell types, which play a role in mnemonic and executive dysfunction during the progression of AD.